The Effect of Biodiesel Policies on World Oilseed Markets and Developing Countries - de Gorter, Harry; Drabik, Dusan; Timilsina, Govinda R. (World Bank, Washington, DC, 2013)
Using an empirical model, this study provides some insights into the functioning of the oilseed-biodiesel-diesel market complex in a large country that determines the biodiesel price, reflecting market equilibrium changes resulting from volatility in the crude oil price. Oilseed crushing produces joint products -- oil and meal -- and this weakens the link between the biodiesel and oilseed feedstock prices. Higher crude oil prices increase biodiesel prices if biofuel benefits from a fuel tax exemption, but lower them with a blending mandate (minimum biofuel content requirement in marketed fuel). When both canola and soybeans are used to produce biodiesel, an increase in the crude oil price leads to higher canola prices, but the effect on soybean prices is ambiguous and depends on relative elasticities of meal demand and canola supply because canola produces more oil than soybeans. An oil price shock with a blending mandate results in a smaller change in oilseed prices compared with a fuel tax exemption. Jumps in world crude oil prices have differential impacts on commodity prices and welfare in developing countries, depending on which policy determines the biodiesel price in OECD countries.